Beyond Narrative (Edition Kulturwissenschaft, 2022)
This book calls for an investigation of the ›borderlands of narrativity‹ — the complex and culturally productive area where the symbolic form of narrative meets other symbolic logics, such as data(base), play, spectacle, or ritual. It opens up a conversation about the ›beyond‹ of narrative, about the myriad constellations in which narrativity interlaces with, rubs against, or morphs into the principles of other forms. To conceptualize these borderlands, the book introduces the notion of »narrative liminality,« which the 16 articles utilize to engage literature, popular culture, digital technology, historical artifacts, and other kinds of texts from a time span of close to 200 years.